Developing a Scale to Measure a Football Players Transfer Score - Gürsakal, Necmi; Çobanoğlu, Halil Orbay; Batmaz, Bülent; Çağlıyor, Sandy; Yılmaz, Fırat Melih (Journal of Sports Research, 2019)
The aim of this study is to develop a scale that demonstrates the transfer score of a football player, with the help of metrics generated through network science. Six matches played Turkish National Football Team in the 2014 World Cup Qualifiers were analyzed with e-analysis soccer program. To obtain the network of the matches and the measurements of networks we used the open-source program Gephi. By taking into consideration the correlations between 11 network metrics, factor analysis was performed, and factor loadings were obtained. To determine the transfer score, as a measure of centralization: degree, weighted-degree and betweenness-centrality, and as a measure of contravention: eccentricity, 4 variables were defined. As a result of factor analysis, three variables were combined into a single component. The variance explanation value was found to be 90.611%, the internal consistency criterion was 0.66 and the transfer score value was calculated using the squares of factor loadings. The scale we developed will be able to determine the transfer value of a player, as well as the changes in the player's performance over time.